Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: (2x-3)(3x+6)>0
=>(2x-3)(x+2)>0
=>x<-2 hoặc x>3/2
b: (3x+4)(2x-6)<0
=>(3x+4)(x-3)<0
=>-4/3<x<3
c: (3x+5)(2x+4)>4
\(\Leftrightarrow6x^2+12x+10x+20-4>0\)
\(\Leftrightarrow6x^2+22x+16>0\)
=>\(6x^2+6x+16x+16>0\)
=>(x+1)(3x+8)>0
=>x>-1 hoặc x<-8/3
f: (4x-8)(2x+5)<0
=>(x-2)(2x+5)<0
=>-5/2<x<2
h: (3x-7)(x+1)<=0
=>x+1>=0 và 3x-7<=0
=>-1<=x<=7/3
\(35\frac{1}{6}:\left(-\frac{4}{5}\right)-46\frac{1}{6}:\left(-\frac{4}{5}\right)\)
\(=\left(35\frac{1}{6}-46\frac{1}{6}\right):\left(-\frac{4}{5}\right)\)
\(=-11:\left(-\frac{4}{5}\right)\)
\(=\frac{55}{4}\)
211/6:(-4/5)-277/6:(-4/5)
(211/6-277/6):(-4/5)
11:(-4/5)
11.(-5/4)
-55/4
C.\(\frac{4^5.\left(1+1+1+1\right)}{3^5.\left(1+1+1\right)}.\frac{6^6}{2^{5+}2^5}=\frac{4^6}{3^6}.\frac{6^6}{2^5+2^5}=\frac{24^6}{3^6.\left(2^5+2^5\right)}=\frac{8^6}{2^5.\left(1+1\right)}\)=\(\frac{8^6}{2^6}\)=4^6=4096